Effect of raw material substitution on the facility location decision under a carbon tax policy - Y. Mechouar; Vincent Hovelaque; Carl Gaigné (EURO Journal on Transportation and Logistics (EJTL), 2022)
Current environmental issues that have been made unavoidable by environmental regulations have become new constraints for industrial companies. In this paper, we consider a joint production-location problem for supply chains under a carbon tax policy on transport-related carbon emissions. We characterize the relationship that links the production level to the input quantities by considering a production function, namely, constant elasticity of substitution (CES) function. Our study focuses on the potential impact of increased transportation costs due to carbon taxation on the joint production-location decision. We find that the location-production configuration differs according to the degree of substitutability among the raw material quantities. More importantly, we observe that a higher carbon tax is more likely to cause a significant jump in firm location choice and a considerable change in production decisions when a firm has high flexibility in its ability to substitute among input quantities.
Keywords: 330; Facility location; Raw material substitution; Environmental issues; Carbon tax